Жизнь человека как предмет философского освоения - Арцишевський, Роман Антонович; Artsyshevskyi, Roman A. (Санкт-Петербургский Центр истории идей, 2002)
Бурное развитие знаний о человеке требует осмысления этих знаний на философско-теоретическом уровне. Одной из форм такого осмысления должна стать виталогия - философское учение о жизни человека, которое является составной частью философской антропологии.

The rapid development of social sciences needs a generalizayion of the received knowledge on the level of philosophical theory. Vitalogy is the result of such generalization. Vitalogi is a philosophical science about human life and is considered to be a part of philosophical anthropology.
Human Life as a Obhekt of Philosophical Teaching
Keywords: виталогия; жизнь человека; наука; философская антропология; vitalogy; human life; science; philosophical antropology